Prototype development and performance analysis of latent heat thermal battery integrated with solar collector / Farhood Sarrafzadeh Javadi - Farhood Sarrafzadeh , Javadi (2022)
Thermal battery is one of the challenging topics due to its low thermal storage capability and independency from the energy sources. This study aims designing, modeling and performing the experimental analysis of a standalone latent heat thermal battery (LHTB) integrated with a solar collector as the main source of heat. The LHTB consists of a plate-fin and tube heat exchanger located inside the battery casing and paraffin wax which is used as a latent heat storage material. Solar thermal energy is absorbed by solar collector and transferred to the LHTB using water as heat transfer fluid (HTF). As a result, the paraffin transforms from the solid to liquid and the heat is stored in the form of latent heat. Then, the heat can be released in a reverse process. The significances of this design are the compatibility with different types of solar collectors which makes it a cheaper solution compared to replacement of solar collector, adaption with different kinds of heat source such as solar heat and industry heat waste, and mobility which allows the user to recover the heat in a place other than charging location. The charging and discharging tests have been conducted in three different operating temperature of 68, 88, and 108 °C and each test was repeated for HTF flow rates of 30, 60 and 120 l/h. The highest amount of stored thermal energy was 13,210 kJ versus the highest recovered amount of 5,825 kJ at maximum recovery efficiency of 35%. However, the highest charging efficiency of 29% achieved in the test using 30 l/h of HTF at 108 °C with stored thermal energy of 11,189 kJ. The recovery efficiency of the LHTB is varies between 18% and 35%. It is highlighted that around two third of the paraffin remained at the temperature above 58 °C at the end of the discharging tests. This is a considerable amount of unused heat trapped inside the paraffin. Thermodynamic analysis confirmed that the highest charging and recovery exergy efficiency of 93.4% and 35.9% are achieved in the tests using 30 l/h of HTF at 68 °C and 120 l/h of HTF at operating temperature of 108 °C, respectively. However, the highest overall exergy efficiency of 25% achieved in the test using 120 l/h of HTF at operating temperature of 68 °C. In the improved LHTB design, the best performance achieved by absorbing 12,647 kJ thermal energy at efficiency of 11% using 120 l/h of HTF at 88 °C. But, highest efficiency of 37% recorded in the test using 30 l/h of HTF. The highest efficiency of 34%-42% in different tests was reported for the HPSC-LHS, as the most advanced design in this field. The similar range of charging and recovery efficiency of 34% and 37% were respectively calculated for the improved LHTB design. The significant result shows that the charging rate advancement is from 2.07 MJ/h in HPSC-LHS to 3.16 MJ/h in LHTB design. Therefore, an increase of 52.3% in charging rate is proven.